If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(z+3)=4
We simplify the equation to the form, which is simple to understand
4(z+3)=4
Reorder the terms in parentheses
+(+4z+12)=4
Remove unnecessary parentheses
+4z+12=+4
We move all terms containing z to the left and all other terms to the right.
+4z=+4-12
We simplify left and right side of the equation.
+4z=-8
We divide both sides of the equation by 4 to get z.
z=-2
| 24x-1+20x+5= | | 454=y*16 | | 5x=x+40 | | 10z-(7+6Z)=3Z+82 | | (a+5)/0.6=10 | | -49=-14d+23 | | 25.5+0.1=P | | 0.4n=4+0.9n | | 3m-6=-4+4m | | 5x+9y=-12 | | -106+2x+5x=34 | | -9=3y+12 | | 55y+5=1050x+10 | | 5+7x=5x+3 | | 19.4-0.6c=-16.6 | | 255-10n=p | | 38=-9x-17 | | 132+x+139= | | n-5=2n | | x+4/7=-2 | | 75+11x-2= | | 3y+6=2y | | m=n+9 | | p=10n-255 | | 6(t-6)+8t=7(27+5)-10 | | 1.43=0.4y-0.6y | | -5=x+12 | | 3x^2+19x+10=0 | | 11.5+0.9h=24.1 | | -p+3+2.4p-2p= | | 1-49c^2=0 | | 12x+17+-1+14x= |